THE INFLUENCE OF TOURISM SECTOR INCOME AND TRADE SECTOR INCOME ON REGIONAL ORIGINAL INCOME IN NORTH ACEH DISTRICT - Afrizal, Afrizal; Anwar, Khairil (LPPM Universitas Malikussaleh, 2025)
The purpose of this study is to investigate how revenues from the tourism and trade sectors affect local original income in the North Aceh Regency. Time series data were used in this study. Between the years 2000 and 2023, the study was carried out in the North Aceh Regency. Multiple linear regression analysis was used for the data analysis. The preliminary findings indicate that revenues from the tourism industry have no effect on the initial regional income of the North Aceh Regency. Revenues from the trade sector have a positive and significant impact on the initial regional income of the North Aceh Regency. The North Aceh Regency's local income is positively and significantly impacted simultaneously by tourism and trade sector revenues..